Opportunities and challenges Economic growth and development in the context of natural resources and energy - Amir, Nurkhaeriah (Journal of Economic Growth and Development Review, 2024)
Natural resources and energy are essential factors for economic growth and development. However, unsustainable use of natural resources and energy can harm the environment and human health. Sustainable use of natural resources and energy can increase economic growth and development. In addition, this article also discusses the challenges of sustainable use of natural resources and energy. One solution is the development of environmentally friendly technology. In addition, the state can encourage companies to use natural resources and energy sustainably.